La autoevaluación del estudiante y su aplicación en el séptimo grado del área de lengua y literatura, bloque 6 “la historieta” de la escuela municipal “Borja”, de la ciudad de Loja, periodo lectivo 2013- 2014 - Medina Carrión, Silvia Johana (2015)
This research entitled: SELF-ASSESSMENT OF STUDENT AND ITS APPLICATION IN THE AREA SEVENTH GRADE LANGUAGE ARTS, BLOCK 6 "CARTOON" MUNICIPAL SCHOOL "BORJA" SUCRE PARISH, CANTON AND PROVINCE OF LOJA, SCHOOL YEAR 2013 - 2014. The overall objective: To determine the level of self-assessment applied by the seventh graders in the area of Language Arts block 6 "cartoon" Municipal School "Borja" in the province of Loja, academic year 2013-2014 to encourage and promote the quality and warmth of the Autonomous learning process. This research is quasi - experimental development and comprehensive, analytical, deductive, scientific, bibliographic, participatory approach, proactive workshop model and comprehensive evaluation was used; between technique and instrument that was used consisted of a survey with the respective same questionnaire applied to teachers and students of the Seventh Grade Basic General Education. After the analysis and interpretation of the results, it was determined that: Students do not have a knowledge environment that is self-assessment, have adequate knowledge of the various techniques and existing self-assessment instruments nor can they recognize the importance of involving the implementation of self-assessment for the acquisition of autonomous learning such results could be verified through the application of the survey to all 13 Seventh grade students basic general education; so it is concluded that lack of implementation of self-assessment to improve autonomous learning in students and by teachers in promoting adequate space, there is low level of academic achievement and poor school dynamics when applying this process, affecting a poor education and warmth.